Peas and beans - Biddle, A. J. (Crop production science in horticulture ;, 2017)
Focusing on peas and beans of agricultural and economic importance, this book includes an introduction to the botanical family, history and production areas of these crops. It also provides detailed information on genetics, seed management, crop protection, growth, crop stresses, harvesting and storage, nutrition and production statistics.